'Eventless' InsP3‐dependent SR‐Ca2+ release affecting atrial Ca2+ sparks. (4th March 2013) - Horn, Tamara; Ullrich, Nina D.; Egger, Marcel
Key points Inositol 1, 4, 5‐trisphosphate receptors (InsP3Rs) are functionally expressed in cardiac myocytes. The influence of inositol 1, 4, 5‐trisphosphate‐induced sarcoplasmic reticulum (SR)‐Ca2+release (IP3ICR) on atrial excitation‐contraction coupling (ECC) under physiological and pathophysiological conditions remains elusive. The present study focuses on local IP3ICR and its functional consequences for ryanodine receptor (RyR) activity and subsequent Ca2+‐induced Ca2+ release in atrial myocytes. Here we show significant SR‐Ca2+ flux, but eventless SR‐Ca2+ release through InsP3Rs. We suggest a new mechanism based on eventless and highly efficient InsP3‐dependent SR‐Ca2+ flux as a crucial mechanism of functional cross‐talk between InsP3Rs and RyRs, which may be an important factor in the modulation of ECC sensitivity. Abstract Augmented inositol 1, 4, 5‐trisphosphate receptor (InsP3R) function has been linked to a variety of cardiac pathologies, including cardiac arrhythmia. The contribution of inositol 1, 4, 5‐trisphosphate‐induced Ca2+ release (IP3ICR) in excitation‐contraction coupling (ECC) under physiological conditions, as well as under cellular remodelling, remains controversial. Here we test the hypothesis that local IP3ICR directly affects ryanodine receptor (RyR) function and subsequent Ca2+‐induced Ca2+ release in atrial myocytes. IP3ICR was evoked by UV‐flash photolysis of caged InsP3 under whole‐cell configuration of the voltage‐clamp technique in atrial myocytes isolated from C57/BL6 mice. Photolytic release of InsP3 was accompanied by a significant increase in the Ca2+ release event frequency (4.14 ± 0.72 vs. 6.20 ± 0.76 events (100 μm)−1 s−1). These individual photolytically triggered Ca2+ release events were identified as Ca2+ sparks, which originated from RyR openings. This was verified by Ca2+ spark analysis and pharmacological separation between RyR and InsP3R‐dependent sarcoplasmic reticulum (SR)‐Ca2+ release (2‐aminoethoxydiphenyl borate, xestospongin C, tetracaine). Significant SR‐Ca2+ flux but eventless SR‐Ca2+ release through InsP3R were characterized using SR‐Ca2+ leak/SR‐Ca2+ load measurements. These results strongly support the idea that IP3ICR can effectively modulate RyR openings and Ca2+ spark probability. We conclude that eventless and highly efficient InsP3‐dependent SR‐Ca2+ flux is the main mechanism of functional cross‐talk between InsP3Rs and RyRs, which may be an important factor in the modulation of ECC sensitivity.